Endophytic Bacillus altitudinis Strain Uses Different Novelty Molecular Pathways to Enhance Plant Growth - Zhang, Dening; Xu, Hongli; Gao, Jingyao; Portieles, Roxana; Du, Lihua; Gao, Xiangyou; Borroto Nordelo, Carlos; Borrás-Hidalgo, Orlando (Frontiers in Microbiology, 2021)
The identification and use of endophytic bacteria capable of triggering plant growth is an important aim in sustainable agriculture. In nature, plants live in alliance with multiple plant growth-promoting endophytic microorganisms. In the current study, we isolated and identified a new endophytic bacterium from a wild plant species Glyceria fluitans. The bacterium was designated as a Bacillus sp. strain using 16S rDNA sequencing. The endophytic Bacillus sp. had a notable influence on plants growth. Results of our assays revealed that the endophytic Bacillus sp. raised the growth of different plant species. Remarkably, we found transcriptional changes in plants treated with the bacterium. Genes such as maturase K, TPR-like superfamily protein, LOB domain-containing protein, and BTB/POZ / TAZ domain-containing protein were highly expressed. In addition, we identified for first-time the induction in the endophytic bacterium of MFS transporter and DNA gyrase subunit B genes during interaction with the plant. These new findings show that endophytic Bacillus sp. could be used as a favourable candidate source to enhance plants growth in sustainable agriculture.